THE ROLE OF POLRI THROUGH BHABINKAMTIBMAS IN EMPOWERING FARMER GROUP COMMUNITIES IN BUILDING FOOD SECURITY - Novalia, Mutia Sari; Romli, Khomsahrial; Ruslan, Idrus; Setiawati, Rini (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Police as a tool of the state to maintain security and order, is one of the pillars for achieving national development goals. Polri through Bhabinkamtibmas carries out community empowerment, especially in organic farmer group communities between Polri institutions and the people in their communities. The data collection method used is the method of observation (observation), interviews and documentation in the form of books, dissertations, journals or others that discuss and review research problems. The results of this study conclude that Polri through Bhabinkamtibmas plays an important role in community empowerment, especially community groups farmers as directors and movers in terms of: planning programs, implementing programs, involvement, socialization, mentoring, training, field visits and the realization of food security.